1991
DOI: 10.1083/jcb.113.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Microtubular organization and its involvement in the biogenetic pathways of plasma membrane proteins in Caco-2 intestinal epithelial cells.

Abstract: Abstract. We characterized the three-dimensional organization of microtubules in the human intestinal epithelial cell line Caco-2 by laser scanning confocal microscopy. Microtubules formed a dense network ",,4-/zm thick parallel to the cell surface in the apical pole and a loose network 1-/zm thick in the basal pole. Between the apical and the basal bundles, microtubules run parallel to the major cell axis, concentrated in the vicinity of the lateral membrane. Colchicine treatment for 4 h depolymerized 99.4 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(160 citation statements)
references
References 64 publications
11
148
1
Order By: Relevance
“…Upon reestablishing secretory flow from the ER to the Golgi in this manner, transport from dispersed Golgi sites to the cell surface, as shown by occurs efficiently, but is no longer directed to specific regions of the cell surface. This interpretation offers a reasonable explanation to the conflicting data regarding the role of microtubules in secretion, where some studies have shown no effect of microtubule disruption Van De Moortele et al, 1993), while others have found significant effects (Redman et al, 1978;Boyd et al, 1982;Breitfield et al, 1990;Gilbert et al, 1991;Rennison et al, 1992). It also supports studies of Saraste and Svensson (1991) that suggested that ER-to-Golgi transport intermediates use microtubules to translocate into the Golgi region.…”
Section: Golgi Fragmentationmentioning
confidence: 90%
“…Upon reestablishing secretory flow from the ER to the Golgi in this manner, transport from dispersed Golgi sites to the cell surface, as shown by occurs efficiently, but is no longer directed to specific regions of the cell surface. This interpretation offers a reasonable explanation to the conflicting data regarding the role of microtubules in secretion, where some studies have shown no effect of microtubule disruption Van De Moortele et al, 1993), while others have found significant effects (Redman et al, 1978;Boyd et al, 1982;Breitfield et al, 1990;Gilbert et al, 1991;Rennison et al, 1992). It also supports studies of Saraste and Svensson (1991) that suggested that ER-to-Golgi transport intermediates use microtubules to translocate into the Golgi region.…”
Section: Golgi Fragmentationmentioning
confidence: 90%
“…In vivo, however, cells are tightly packed together, epithelial cells are apicobasally polarized, and microtubule minus ends are oriented toward the apical membrane (11,17,18). Therefore, it will be interesting to determine whether CAMSAPs can also regulate the orientation of microtubules in polarized epithelial cells; such studies are actually under way.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Caco-2 cells closely resemble normal intestinal cells in that they express intestinal hydrolases such as sucrase-isomaltase and alkaline phosphatase. Furthermore, these cells are similar to native intestinal epithelial cells in that they have receptors for prostaglandins, growth factors, vasoactive intestinal peptide, low-density lipoprotein, insulin, and specific substrates such as dipeptides, fructose, glucose, hexoses, and vitamin B 12 (Gilbert et al, 1991;Meunier et al, 1995;Banan et al, 1998b). Accordingly, this cell line provides a suitable in vitro model for our studies.…”
Section: Methodsmentioning
confidence: 99%
“…Caco-2 cells were obtained from American Type Culture Collection (Manassas, VA) at passage 15. This widely used colonic cell line was chosen for our studies because they form monolayers that morphologically resemble intestinal cells, with defined apical brush borders and tight junctions, and a highly organized claudin-ring network upon differentiation (Gilbert et al, 1991;Meunier et al, 1995;Banan et al, 1998b). Caco-2 cells are a transformed cell line, and monolayers of tumor cells may respond differently than do nontransformed cells, including enterocytes in native tissue.…”
Section: Methodsmentioning
confidence: 99%